ANALYSIS OF ELECTRICAL FAULTS IN THE CRANE HOISTING CONTROL PANEL AT THE SEI DAUN PTPN 3 PALM FACTORY - Fahrul Ramadhan; Eddy Sutejo; Muhammad Rizki Syahputra (Journal of Engineering, Electrical and Informatics, 2024)
The frequent issues encountered in the palm oil processing process at PTPN 3 Sei Daun primarily involve electrical disruptions in the hoisting crane control panel. These damages have adverse repercussions for the company, resulting in production halts. The objective of this research is to analyze the root cause of the issue and subsequently determine maintenance and efforts to anticipate these disruptions. One of the problems that often occurs is a damaged contactor, which results in it stopping the operation of the hoisting crane itsel. The expected outcome of this research is to minimize the occurring damage, optimize maintenance, and prevent breakdowns, allowing the company to optimize its palm oil processing.